The Differences in the Importance of Upbringing Tolerance in a Chinese Family Across Generations - Liubov Ryumshina; Anastasiya Chernova; Elena Zinchenko; Ziyoda Abidova; Yuliya Berdyanskaya; Olga Batychko (Primenjena Psihologija, 2025)
The article uses China as an example to demonstrate the importance and possibility of taking big data into account when studying intergenerational relationships during a period of great change. The aims of the study were to examine the importance of nurturing tolerance in children in Chinese families. To ensure representativeness, different generations of adults who live in diverse socio-economic conditions were included in the study. The study used the World Values Survey (WVS) database (China’s participation from 1990 to 2018), and the sample included 14,489 respondents. According to the results of the frequency analysis, tolerance ranks 2-5 (depending on the year of the study) among the qualities important for nurturing in a Chinese family. The qualities that Chinese respondents rate as more important for raising children than tolerance include independence and diligence. The highest value for the importance of nurturing tolerance in the family was recorded in 2001, but since 2007, a statistically significant downward trend has been established. Respondents under 29 often rate tolerance higher than respondents aged 30-49 and over 50.